Respuesta :
Solution:
The Expression containing variables raised to power i.e Radicals means combination of base and Exponent is
[tex]\frac{(x y^{4})^{-3}}{(x^{-5} y^{5})^{?}}[/tex]
As while solving these kind of problems, keep in mind the following radical rules:
[tex]1. (a^m)^{n}=a^{mn}\\\\2.(ab)^{m}=a^mb^n\\\\3.(a^{m})^{-n}=a^{-mn}[/tex]
[tex]\frac{(x y^{4})^{-3}}{(x^{-5} y^{5})^{?}}[/tex]
= [tex]\frac{x^{-3}y^{-12}}{(x^{-5}y^{5})^{?}}[/tex]
So, the first step is in simplifying the expression is Option B which is →→x to the power of negative 3 multiplied by y to the power of negative 12, the whole over x to the power of negative 5 multiplied by y to the power of 5.